ChatGPT as a New Frontier in Arabic Education Technology - Islamiyah Sulaeman; Syuhadak Syuhadak; Insyirah Sulaeman (Universitas Negeri Malang, 2023)
Artificial intelligence is a technology that is believed to be capable of emulating human intelligence, and one area where its potential is being explored is the use of ChatGPT in the Arabic language education sector. Therefore, this study aims to analyze the challenges and opportunities of using ChatGPT in Arabic language education as a form of actual educational technology. This study uses the library research method, with primary and secondary data sources obtained from previous literature relevant to the research topic. Data collection was carried out by editing, organizing, and founding techniques. Data analysis was carried out using data reduction techniques, data presentation, and drawing conclusions. The results of this study show that ChatGPT has the potential to be a valuable tool for developing Arabic language education, but there are challenges that must be addressed to ensure its effective use by students and teachers and to avoid any negative implications. This research provides insights for the future development of learning technologies, enabling the use of ChatGPT in education to provide maximum benefits for students and teachers.